2023
DOI: 10.1002/ncp.11055
|View full text |Cite
|
Sign up to set email alerts
|

Blenderized tube feedings: Practice recommendations from the American Society for Parenteral and Enteral Nutrition

Lisa Epp,
Allison Blackmer,
April Church
et al.

Abstract: Prior to the 1970s, blending food and liquids and putting them through an enteral access device (EAD) was the most common form of enteral nutrition (EN). However, in the 1970s, blenderized tube feedings (BTFs) became less popular due to the emergence of modern commercial enteral formulas (CEFs). Recently, a cultural shift toward consuming a natural diet, consisting of whole foods, has led to a resurgence in the use of BTF. The increasing use of BTF in a variety of patient care settings identifies a need for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
(177 reference statements)
0
5
0
Order By: Relevance
“…Although BTF use remains primarily driven by patient/ caregiver requests, a shared decision-making model is necessary to ensure patients/caregivers have the information required to make an informed decision. 3 RDN/Is should seek evidence-based BTF-related education/training, screen all enteral nutrition-fed patients for a desire to use BTFs, learn to develop client-specific BTF recipes, and counsel patients on food safety techniques to prevent microbial contamination and feeding tube occlusions. ASPEN, the Academy of Nutrition and Dietetics, and other leading nutrition organizations have an opportunity and obligation to develop BTFspecific education/training (eg, webinars, conferences, and workshops), evidence-based toolkits, and other resources to strengthen HCPs' knowledge and competence to better support patients/caregivers who desire to use BTFs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although BTF use remains primarily driven by patient/ caregiver requests, a shared decision-making model is necessary to ensure patients/caregivers have the information required to make an informed decision. 3 RDN/Is should seek evidence-based BTF-related education/training, screen all enteral nutrition-fed patients for a desire to use BTFs, learn to develop client-specific BTF recipes, and counsel patients on food safety techniques to prevent microbial contamination and feeding tube occlusions. ASPEN, the Academy of Nutrition and Dietetics, and other leading nutrition organizations have an opportunity and obligation to develop BTFspecific education/training (eg, webinars, conferences, and workshops), evidence-based toolkits, and other resources to strengthen HCPs' knowledge and competence to better support patients/caregivers who desire to use BTFs.…”
Section: Discussionmentioning
confidence: 99%
“…10,[13][14][15] There are a lack of randomized controlled trials comparing CEFs with BTFs; however, observational studies indicate BTFs are associated with improved health outcomes and quality of life, such as decreased hospital use and increased patient satisfaction compared with CEFs. 3,16,17 More recent studies have shown that BTFs are safe and well tolerated. [18][19][20] Barriers to BTF use include the need for a specialized blender, time and labor involved in preparing BTFs, cost, difficulty managing BTFs away from home, concerns caused by commercial insurance coverage, and inadequate support from the family or HCP.…”
Section: Btf Benefits and Barriersmentioning
confidence: 99%
See 3 more Smart Citations